2020
DOI: 10.1088/1742-6596/1676/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Characteristic Research on Orthogonal Cutting the Plastic Metal Material-C10100 with Negative Rake Angle Tool

Abstract: With the high-speed development of the delicateness grinding, mechanical scratching and micro-cutting technology, scholars have become more and more interested in the forming mechanism and related characteristics of the negative rake angle tool. Based on DEFORM-2D forming software, this paper investigates the forming mechanism and related characteristics of the negative rake angle tool. Through the simulation comparison analysis, it is clear that as the negative rake angle decreased form 0° to 60° (the negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Subsequent material flow will move along the edges of this zone towards both sides, a direction also indicated by the material flow in figure 7. The microhardness within the stagnation zone tends to align with that of the base material [14]. The initial hardness of T2 copper is 80 HV, and the hardness is increased after machining because the laserassisted imprint machining technology differs from orthogonal turning in that the lower boundary is not an open boundary condition, but is supported by a hard substrate.…”
Section: Critical Cone Angle Yielding the Stagnation Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent material flow will move along the edges of this zone towards both sides, a direction also indicated by the material flow in figure 7. The microhardness within the stagnation zone tends to align with that of the base material [14]. The initial hardness of T2 copper is 80 HV, and the hardness is increased after machining because the laserassisted imprint machining technology differs from orthogonal turning in that the lower boundary is not an open boundary condition, but is supported by a hard substrate.…”
Section: Critical Cone Angle Yielding the Stagnation Zonementioning
confidence: 99%
“…The results of Ozturk [12] and Anilchandra [13] have shown that the creation of stagnation zone improves the surface quality of the workpiece. Ding [14] discovered that the hardness of the machined surface within the stagnation zone was notably lower compared to that within the plastic flow zone during scratching. This finding suggests that the influence of the stagnation zone can mitigate the extent of work hardening and strain strengthening of the material surface.…”
Section: Introductionmentioning
confidence: 99%